2010
DOI: 10.1021/ie1000983
|View full text |Cite
|
Sign up to set email alerts
|

Acidolysis of Wood in Ionic Liquids

Abstract: Three wood species including Eucalyptus grandis (E. grandis), Southern pine (S. pine), and Norway spruce thermomechanical pulp (N. spruce TMP) were dissolved in the ionic liquid (IL) 1-allyl-3-methylimidazolium chloride ([Amim]Cl), and then they were pretreated with small amounts of hydrochloric acid, as a function of time. The materials regenerated from the IL solutions were determined to contain significantly higher amounts of lignin than the original wood. Detailed analyses of the recovered IL revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 40 publications
(100 reference statements)
2
45
0
Order By: Relevance
“…Several examples have been published, with the inevitably degraded lignin typically being isolated at the end but not considered further. The IL employed most commonly is [Bmim]Cl [64,65] or structurally similar imidazolium chloride analogues, [66,67] and although a range of acids have been investigated, HCl is the most common. [65][66][67] The one-pot catalyzed reaction of pine wood dissolved in [Bmim]Cl in the presence of CrCl 3 Á 6H 2 O as catalyst resulted in self-condensation between the lignin and the glucose conversion products to yield 'sugar-derived humin', a polymeric product and potential adsorbent.…”
Section: Direct Conversion Of Cellulose In the Presence Of Ligninmentioning
confidence: 99%
“…Several examples have been published, with the inevitably degraded lignin typically being isolated at the end but not considered further. The IL employed most commonly is [Bmim]Cl [64,65] or structurally similar imidazolium chloride analogues, [66,67] and although a range of acids have been investigated, HCl is the most common. [65][66][67] The one-pot catalyzed reaction of pine wood dissolved in [Bmim]Cl in the presence of CrCl 3 Á 6H 2 O as catalyst resulted in self-condensation between the lignin and the glucose conversion products to yield 'sugar-derived humin', a polymeric product and potential adsorbent.…”
Section: Direct Conversion Of Cellulose In the Presence Of Ligninmentioning
confidence: 99%
“…Researchers have reported the ability to obtain 5-HMF and glucose by rapid hydrolysis of cellulose dissolved in an ionic liquid at 100°C, using acid catalysts such as sulfuric acid or hydrochloric acid [88][89][90][91]. Other researchers have mentioned production of various types of sugars, such as glucose and xylose, by performing acid hydrolysis of wood in ionic liquids containing various acid catalysts such as sulfuric, hydrochloric or trifluoroacetic acid [92][93][94]. It was also found that 5-HMF and furfural, which are decomposition products of sugars promising raw materials for polymer production, can be obtained during such hydrolysis reactions.…”
Section: Depolymerization and Conversion To Useful Chemicalsmentioning
confidence: 99%
“…Over the past few decades, a large number of research efforts have focused on the cellulose, because cellulose is the most abundant renewable biomass in the world, and it can be converted into biofuels, such as ethanol after cellulose is degraded to sugar (Huang et al, 2011). Many methods have been used for the degradation of cellulosic materials to sugars, such as acidolysis (Li et al, 2010), alkaline hydrolysis (Carrillo et al, 2005) and enzymatic hydrolysis (Park et al, 2002). Among these methods, the enzymatic hydrolysis has received great attention due to the fact that the enzymatic process has the potential to convert the lignocellulosic materials to ethanol with a high yield and low production cost (Wingren et al, 2003;Galbe and Zacchi, 2002;Kannan and Jasra, 2011).…”
Section: Introductionmentioning
confidence: 99%